Impact of suspended sediment on the behavior of polycyclic aromatic hydrocarbons in the Yellow River: Spatial distribution, transport and fate. (November 2018) - Feng, Jinglan; Hu, Pengtuan; Su, Xianfa; Li, Qilu; Sun, Jianhui; Li, Yi-Fan
Abstract: A total of 150 samples were collected from 25 sites in the Yellow River of Henan Province during 2014 to demonstrate the impact of suspended sediment (SS) load on the behavior of semi-volatile organic compounds (SVOCs) in the Yellow River. The average concentrations of SS ranged from <0.01 g/L to 1.7 g/L and the total loading/removal of SS was 108 Mt in the Henan section of the Yellow River. The sixteen polycyclic aromatic hydrocarbons (PAHs) were detected with concentrations of 23-370 ng/L in the dissolved phase and 36–3700 ng/g dw in the particulate phase, respectively. The concentrations of ∑16 PAHs (sum of PAHs in the dissolved and particulate phase) along the river flow showed a decreasing trend and then an increasingly varied SS concentration. In the SS-abundant section, PAHs were released from the particle phase to the dissolved phase. Based on the mass balance of water and SS, 43% of the total load of PAHs is ascribed to the scouring processes, indicating that PAHs release from river-bed soil to the Yellow River is significant. Highlights: Impact of SS on the transport of PAHs in the Yellow River was investigated. Increase of SS concentrations mainly caused by the river scouring. The releasing process of PAHs from SS to water was verified by the calculation of fugacity. Transport fluxes of PAHs were calculated in the Yellow River.